A simplified semi-numerical model to simulate a U-pipe ground heat exchanger. (3rd March 2020) - Wang, Changlong; Huang, Zhijia; Lu, Yuehong; Huang, Xinjie; Fang, Han
Abstract: A simplified semi-numerical model is developed to simulate a U-pipe ground heat exchanger (GHE), including a 2-D numerical model to simulate the radial and axial heat transfer in the borehole and an infinite cylindrical-source model to analyze the radial heat transfer in the soil. The proposed model is verified by comparing the calculated results with experimental data, simulation data, and the results of other models. The temperature distributions of the borehole and the soil calculated by the proposed model match well with experimental data and simulation data. The proposed model is demonstrated to have an accurate calculation of temperature distributions compared with other models.